Promoter Methylation-Regulated miR-145-5p Inhibits Laryngeal Squamous Cell Carcinoma Progression by Targeting FSCN1 - Gao, Wei (Mol Ther, 2019)
Laryngeal squamous cell carcinoma (LSCC) is a common form of head and neck cancer with poor prognosis. However, the mechanism underlying the pathogenesis of LSCC remains unclear. Here, we demonstrated increased expression of fascin actin-bundling protein 1 (FSCN1) and decreased expression of microRNA-145-5p (miR-145-5p) in a clinical cohort of LSCC. Luciferase assay revealed that miR-145-5p is a negative regulator of FSCN1. Importantly, low miR-145-5p expression was correlated with TNM (tumor, node, metastasis) status and metastasis. Moreover, cases with low miR-145-5p/high FSCN1 expression showed poor prognosis, and these characteristics together served as independent prognostic indicators of survival. Gain- and loss-of-function studies showed that miR-145-5p overexpression or FSCN1 knockdown inhibited LSCC migration, invasion, and growth by suppressing the epithelial-mesenchymal transition along with inducing cell-cycle arrest and apoptosis. Additionally, hypermethylation of the miR-145-5p promoter suggested that repression of miR-145-5p arises through epigenetic inactivation. LSCC tumor growth in vivo could be inhibited by using miR-145-5p agomir or FSCN1 small interfering RNA (siRNA), which highlights the potential for clinical translation. Collectively, our findings indicate that miR-145-5p plays critical roles in inhibiting the progression of LSCC by suppressing FSCN1. Both miR-145-5p and FSCN1 are important potential prognostic markers and therapeutic targets for LSCC.